Infradian cardiovascular rhythms and between subject cardiovascular coupling in Mars500 prolonged confinement study - Vigo, Daniel Eduardo (2025)
Fil: Vigo, Daniel Eduardo. Pontificia Universidad Católica Argentina. Instituto de Investigaciones Biomédicas; Argentina